Biological processes modelling for MBR systems: A review of the state-of-the-art focusing on SMP and EPS - Mannina, Giorgio; Ni, Bing-Jie; Makinia, Jacek; Harmand, Jérôme; Alliet, Marion; Brepols, Christoph; Ruano, M. Victoria; Robles, Angel; Heran, Marc; Gulhan, Hazal; Rodriguez-Roda, Ignasi; Comas, Joaquim (Elsevier BV, 2023)
A mathematical correlation between biomass kinetic and membrane fouling can improve the understanding and spread of Membrane Bioreactor (MBR) technology, especially in solving the membrane fouling issues. On this behalf, this paper, produced by the International Water Association (IWA) Task Group on Membrane modelling and control, reviews the current state-of-the-art regarding the modelling of kinetic processes of biomass, focusing on modelling production and utilization of soluble microbial products (SMP) and extracellular polymeric substances (EPS). The key findings of this work show that the new conceptual approaches focus on the role of different bacterial groups in the formation and degradation of SMP/EPS. Even though several studies have been published regarding SMP modelling, there still needs to be more information due to the highly complicated SMP nature to facilitate the accurate modelling of membrane fouling. The EPS group has seldom been addressed in the literature, probably due to the knowledge deficiency concerning the triggers for production and degradation pathways in MBR systems, which require further efforts. Finally, the successful model applications showed that proper estimation of SMP and EPS by modelling approaches could optimise membrane fouling, which can influence the MBR energy consumption, operating costs, and greenhouse gas emissions.
Keywords: [SDE] Environmental Sciences; Membrane bioreactors; química; teoria cinètica dels gasos; Bacteria; Sewage; [SPI] Engineering Sciences [physics]; biomassa; Extracellular Polymeric Substance Matrix; Membranes, Artificial; cinètica química; Extracellular polymeric substances; Biomass kinetic models; [SPI]Engineering Sciences [physics]; Biomass kinetic models Extracellular polymeric substances Membrane bioreactors Soluble microbial products; Soluble microbial products; Bioreactors; [SDE]Environmental Sciences; bioenginyeria; Biomass